The relationship between student athletes' behaviour in the classroom and teachers' burnout level - Karakaya, Yunus Emre; Brusseau, Timothy A.; Karademir, Tamer (Walter de Gruyter Gmbh, 2015)
Study aim: To examine the relationship between the behaviour of student athletes in the classroom in sport schools in Turkey and their teachers' burnout level. Material and methods: The sample of the study consisted of 226 teachers from sport high schools in Turkey. A questionnaire developed by Ozdemir (2009) was used to ascertain students' unwanted behaviour and the Maslach burnout inventory developed by Maslach and Jackson (1981) was used to assess the views of the research group. The data obtained were analysed through the SPSS 18.0 software. Results: The research group complained of student behaviour including 'speaking without permission' during the course, 'not having the necessary equipment for the course', 'not performing a given task' and 'not listening to the teacher'. A positive linear and moderate level relationship was found between the emotional burnout and depersonalization sub-dimensions. Suggesting that, as emotional burnout level increases so does the level of indifference. A positive and linear but low-level relationship was found between the emotional burnout and personal failure sub-dimensions. Suggesting that, as emotional burnout level increases so does personal failure. In addition, a positive and linear but low-level relationship was observed between the depersonalization and personal failure sub-dimensions. In other words, as the level of indifference increases so does personal failure. A significant difference was seen in the period of service variable of the depersonalization sub-dimension in the research group. Significant differences were observed in accordance with personal failure, period of service and fields of study. Conclusions: Teachers should analyse their students in terms of academic and personal development in order to reduce negative behaviours in the classroom. Teachers should be able to help students in whatever field they need. Teachers in sports schools should receive support in adapting to the institutional culture of the schools.
Keywords: Student athlete code of conduct; Burnout; Sports High School Teachers